Role of furfuryl palmitate based new generation emollient as an adjutant in management and maintenance of atopic dermatitis and psoriasis: a case report - Srinivasa, Seema; Katke, Vaishali (International Journal of Research in Medical Sciences, 2025)
Atopic dermatitis (AD) and psoriasis vulgaris are chronic inflammatory skin diseases that impose a significant clinical and psychosocial burden. Sustaining long-term remission and preventing relapse remain persistent challenges. Conventional therapies, while effective, are often limited by side effects and issues with patient adherence. Recent evidence highlights the role of oxidative stress in skin barrier disruption and inflammation, suggesting the potential of antioxidant-based adjunctive therapies. This report describes two clinical cases—one of atopic dermatitis and the other of psoriasis vulgaris—in which a furfuryl palmitate-based, antioxidant-rich emollient was integrated into the treatment plan. In both patients, the emollient was used alongside standard systemic or topical therapies. Both cases showed marked clinical improvement, including reduced lesion severity, rapid itch relief, and extended remission periods without relapse. These findings suggest that oxidative stress modulation through antioxidant emollients like furfuryl palmitate may serve as a valuable adjunct in the long-term management of AD and psoriasis. Adjunctive use may support skin barrier repair, enhance therapeutic outcomes, and reduce the frequency of disease flares. Further clinical studies are warranted to substantiate these observations.